To solve for x, we will first distribute the -2 on the left side of the equation:
-2(3x - 15) = 60
-6x + 30 = 60
Now, we will isolate the variable x by subtracting 30 from both sides:
-6x = 30
-6x = 30 - 30
-6x = 0
Finally, divide both sides by -6 to solve for x:
x = 0 / -6
x = 0
Therefore, the solution is x = 0.
Solve for x . −2(3x−15)=60 (1 point)
7 answers
wrong
Let's try solving it again:
-2(3x - 15) = 60
First, distribute the -2:
-6x + 30 = 60
Now, subtract 30 from both sides:
-6x = 30
Finally, divide by -6 to isolate x:
x = 30 / -6
x = -5
Therefore, the solution for x is -5.
-2(3x - 15) = 60
First, distribute the -2:
-6x + 30 = 60
Now, subtract 30 from both sides:
-6x = 30
Finally, divide by -6 to isolate x:
x = 30 / -6
x = -5
Therefore, the solution for x is -5.
Solve for x . 5(2x−8)=−30 (1 point)
To solve for x, we will first distribute the 5 on the left side of the equation:
5(2x - 8) = -30
10x - 40 = -30
Now, we will isolate the variable x by adding 40 to both sides:
10x = 10
Finally, divide both sides by 10 to solve for x:
x = 10 / 10
x = 1
Therefore, the solution is x = 1.
5(2x - 8) = -30
10x - 40 = -30
Now, we will isolate the variable x by adding 40 to both sides:
10x = 10
Finally, divide both sides by 10 to solve for x:
x = 10 / 10
x = 1
Therefore, the solution is x = 1.
Solve for x : 4(3x+2)+3=35 .(1 point)
To solve for x, we will first simplify the equation:
4(3x + 2) + 3 = 35
12x + 8 + 3 = 35
12x + 11 = 35
Now, we will isolate the variable x by subtracting 11 from both sides:
12x = 35 - 11
12x = 24
Finally, divide both sides by 12 to solve for x:
x = 24 / 12
x = 2
Therefore, the solution is x = 2.
4(3x + 2) + 3 = 35
12x + 8 + 3 = 35
12x + 11 = 35
Now, we will isolate the variable x by subtracting 11 from both sides:
12x = 35 - 11
12x = 24
Finally, divide both sides by 12 to solve for x:
x = 24 / 12
x = 2
Therefore, the solution is x = 2.